KUALITAS PELAYANAN PUSKESMAS MEMPENGARUHI KEPUASAN MASYARAKAT DI PUSKESMAS KALIRUNGKUT KOTA SURABAYA - Firdaus, Sylvia Kurnia; Santoso, Teguh (Universitas 17 Agustus 1945 Surabaya, 2017)
Quality of Puskesmas Service Influence the Community Satisfaction in Puskesmas Kalirungkut Kota Surabaya. Public service as a form of good service both in the public goods, public service and even administrative service that in principle as responsibility and performed by government institution in order to meeting the basic needs of public at large. The government had tried to fulfilled the society needs on health service by established hospitals and Public Health Centres (PUSKESMAS) in whole of Indonesia region. In this case of Puskesmas Kalirungkut Surabaya city conducted various efforts to improve its service quality. This research has purposes to examines the service quality of Puskesmas influencing people satisfaction in Puskesmas Kalirungkut of Surabaya. Focus of the study grounded on five dimension of service quality (SERVQUAL) subject to Parasuraman that are Tangible, Reliability, Responsiveness, Assurance, Empathy. The research method that used is qualitative descriptive. The result of the research showed that are 1) service quality in Puskesmas Kalirungkut of Surabaya seen from dimensions of Tangible, Reliability, Responsiveness, Assurance, Empathy are good. 2) Service conditions in Puskesmas Kalirungkut of Surabaya conducted to the public based on Tangible, Reliability, Responsiveness, Assurance, Empathy get rating of fairy good. 3) People satisfaction on service in Puskesmas Kalirungkut of Surabaya about the people wants on puskesmas services included Tangible, Reliability, Responsiveness, Assurance, Empathy are fairly good in the service managing process then people is satisfied enough. However the people satisfaction does not maximally improved enough due to still found lack in time punctuality and fastness then is necessary to be increased. Keywords: Service quality, Public service, People Satisfaction